Synovial cyst of the thoracic spine: case report - Oliveira,Helio A. (2007)
Spinal cord compressing syndrome due to synovial cyst (SC) of the thoracic spine is a rare clinic condition. We report a case of SC located in the thoracic spine causing spastic paraparesis in a 14 year-old female patient. The SC was removed thoroughly by laminectomy. The patient had an excellent recovery. The etiological and therapeutic aspects are discussed.